Tuberculosis in pediatric antiretroviral therapy programs in low- and middle-income countries: Diagnosis and screening practices - Ballif, M.; Renner, L.; Dusingize, J.C.; Leroy, V.; Ayaya, S.; Wools-Kaloustian, K.; Cortes, C.P.; McGowan, C.C.; Graber, C.; Mandalakas, A.M.; Mofenson, L.M.; Egger, M.; et al. (Journal of the Pediatric Infectious Diseases Society, 2015)
Background. The global burden of childhood tuberculosis (TB) is estimated to be 0.5 million new cases per year. Human immunodeficiency virus (HIV)-infected children are at high risk for TB. Diagnosis of TB in HIVinfected children remains a major challenge. Methods. We describe TB diagnosis and screening practices of pediatric antiretroviral treatment (ART) programs in Africa, Asia, the Caribbean, and Central and South America.We used web-based questionnaires to collect data on ART programs and patients seen from March to July 2012. Forty-three ART programs treating children in 23 countries participated in the study. Results. Sputum microscopy and chest Radiograph were available at all programs, mycobacterial culture in 40 (93%) sites, gastric aspiration in 27 (63%), induced sputum in 23 (54%), and Xpert MTB/RIF in 16 (37%) sites. Screening practices to exclude active TB before starting ART included contact history in 41 sites (84%), symptom screening in 38 (88%), and chest Radiograph in 34 sites (79%). The use of diagnostic tools was examined among 146 children diagnosed with TB during the study period. Chest Radiograph was used in 125 (86%) children, sputum microscopy in 76 (52%), induced sputum microscopy in 38 (26%), gastric aspirate microscopy in 35 (24%), culture in 25 (17%), and Xpert MTB/RIF in 11 (8%) children. Conclusions. Induced sputum and Xpert MTB/RIF were infrequently available to diagnose childhood TB, and screening was largely based on symptom identification. There is an urgent need to improve the capacity of ART programs in low- and middle-income countries to exclude and diagnose TB in HIV-infected children. ©The Author 2014.
Keywords: HIV; Low-income countries; Pediatric; Survey; Tuberculosis